PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN JASA OUTSOURCING PT. RAMA INDONESIA - Rina Nur Fauziah; Imam Wibowo; Hery Wihasnanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
Purpose to analyze the effect of service quality and corporate image on customer satisfaction outsourcing services at PT. Rama Indonesia. This research is included in the category of causal associative research using a quantitative approach. The sampling technique used a saturated sample. All members of the population were sampled, totaling 30 companies using outsourcing services at PT. Rama Indonesia. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in multiple or simple ways the quality of service and corporate image had a positive and significant effect on customer satisfaction of outsourcing service users at PT. Rama Indonesia.